PENINGKATAN PEREKONOMIAN PENGRAJIN BATIK TANAH LIEK “SALINGKA TABEK” SOLOK - Laynita Sari; Renil Septiano; Dewi Zulvia; Febryandhie Ananda (Jurnal Abdimas Bina Bangsa, 2023)
The purpose of this Community Service activity is to improve the economy of the Solok “salingka tabek” clay batik craftsmen. Improving the economy is carried out by providing an understanding of accounting bookkeeping because there are many deficiencies encountered in connection with the recording and reporting of financial transactions. This is caused by the knowledge of the clay batik craftsman "salingka tabek" which is still very limited in the field of Accounting. By using accounting, it is hoped that the recording and reporting of financial transactions of the craftsmen will be more organized so that they can assist management in making decisions and improve the craftsmen’s economy of the "salingka tabek" clay batik industry